2022
DOI: 10.1530/eje-21-1172
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, determinants and costs of thyroid function testing in a laboratory serving a large population

Abstract: Objective: To assess the rationale and frequency of thyroid function testing and to analyse factors that influence serum thyrotropin (TSH) levels. Patients , Design and Main Outcome Measures: Serum TSH levels were evaluated in a hospital laboratory serving a population of 604,000 in 2018. Patients on medications or with conditions affecting thyroid function were excluded. Frequency of thyroid function testing by age and sex was assessed and relationship between serum TSH with potential predictor variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Another study from the UK, however, examining thyroid tests in 161401 individuals, found that TSH concentrations were not a good discriminant of symptoms attributed to thyroid dysfunction. Furthermore, TSH values depended on age, sex, season and timing of sampling, which would require adjustment of TSH reference ranges ( 2 ). Finally, an international online survey of 3915 individuals with self-reported treated hypothyroidism found a 59% prevalence of probable somatic symptom disorder with a tendency to attribute persistent symptoms to hypothyroidism or its treatment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from the UK, however, examining thyroid tests in 161401 individuals, found that TSH concentrations were not a good discriminant of symptoms attributed to thyroid dysfunction. Furthermore, TSH values depended on age, sex, season and timing of sampling, which would require adjustment of TSH reference ranges ( 2 ). Finally, an international online survey of 3915 individuals with self-reported treated hypothyroidism found a 59% prevalence of probable somatic symptom disorder with a tendency to attribute persistent symptoms to hypothyroidism or its treatment ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, body mass index, ethnicity, iodine intake, thyroid peroxidase antibody (TPOAb) status, and TSH cut-off point are among the factors that can affect prevalence estimates (1). Symptoms attributed to SCH are often non-specific, including tiredness/fatigue, cold intolerance, weight gain, cognitive dysfunction, depression, and anxiety (1)(2)(3). These symptoms can significantly affect well-being, leading to repeated medical consultations, request for inappropriate investigations, and dissatisfaction with treatment (3).…”
Section: Introductionmentioning
confidence: 99%
“…There is a modest rise in serum TSH levels with age, yet the TSH reference range does not reflect this age-related increase (5). It is therefore not surprising that the prevalence of SCH rises with age and there is an attenuation of this increase when age-appropriate TSH reference ranges are utilised (6). However, randomised controlled trials of levothyroxine treatment of SCH in older people (>65 years) conducted to date have been proven to be ineffective in improving symptoms of hypothyroidism and/or quality of life (7).…”
mentioning
confidence: 99%